2019
DOI: 10.17564/2316-3801.2019v8n2p239-252
|View full text |Cite
|
Sign up to set email alerts
|

A Feminização Da Velhice: Uma Abordagem Biopsicossocial Do Fenômeno

Abstract: O envelhecimento populacional traz consigo uma série de desafios que exigem a atenção de todos, principalmente do Estado no que tange a implementação de políticas públicas. Diante disso, o presente estudo tem como objetivo levantar a temática da feminização da velhice, um fenômeno resultante da transição demográfica, no qual o número de mulheres com idade maior ou igual à 60 anos se sobressai ao contingente masculino. Trata-se de um ensaio teórico realizado através de levantamento bibliográfico traçando aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 10 publications
2
5
0
26
Order By: Relevance
“…Considering the sociodemographic variables, it was possible to map a population composed predominantly of women -a finding already expected and in agreement with several literatures. 14,15 The prevalence of frailty among elderly women is similar to another population-based survey, 16 in which 11,015 men and women over 60 years of age were followed for two years and assessed for frailty phenotype. The study concluded that there was a specific prevalence of frailty in females, as elderly women are almost twice as likely to be frail as men (16.4% vs. 8.6%), and are also more prone to the risk of frailty.…”
Section: Discussionmentioning
confidence: 55%
“…Considering the sociodemographic variables, it was possible to map a population composed predominantly of women -a finding already expected and in agreement with several literatures. 14,15 The prevalence of frailty among elderly women is similar to another population-based survey, 16 in which 11,015 men and women over 60 years of age were followed for two years and assessed for frailty phenotype. The study concluded that there was a specific prevalence of frailty in females, as elderly women are almost twice as likely to be frail as men (16.4% vs. 8.6%), and are also more prone to the risk of frailty.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it is possible that older men who live by themselves are less likely to adhere to this type of program. Another factor which may explain the mostly female presence in programs such as this is a phenomenon known as the feminization of old age 21 , which occurs due to There are lots of nice people 99 1 0…”
Section: Discussionmentioning
confidence: 99%
“…O que por outro lado, quando associados aos aspectos históricos, socioeconômicos, culturais e geográficos, poderiam contribuir para a maior expectativa de vida das mulheres em nível mundial 15 . A feminização do processo de envelhecimento relaciona-se às demandas em saúde, como a necessidade de profissionais especializados, além de projetos voltados para o cuidado a essa população, envolvendo a orientação para o autocuidado, promoção da participação social e proteção contra violência, de forma a promover um envelhecimento mais saudável 16 .…”
Section: Discussionunclassified